MEDIA MASSA ONLINE DAN KESADARAN SOSIAL GENERASI MILENIAL - Siswanto, Abdul Harif; Haniza, Nurul; Rosyad, Achmad (DE FACTO : Journal Of International Multidisciplinary Science, 2023)
Online mass media that is presented online on the internet website is the "third generation" mass media after printed media, and electronic media. Technically / physically, online mass media is teleco- mmunications and multimedia-based media. The presence of online mass media accompanied by the rapid development of communication and information technology, such as Gadget, a mobile electronic device that can be used to access internet network sites around the world, allows users to obtain various information easily and quickly. The study aims to look at the correlation of online mass media and social awareness of the millennial generation. This explanatory survey method with accidental sampling technique was conducted on MiNews online media with a total sample of 95 readers aged 15 to 35 years (millennial generation). The results showed that MiNews online media coverage received considerable attention and was positively perceived by the millennial generation. Correlation analysis using a linear regression equation model shows that exposure to online media messages has a positive effect on the social awareness of the millennial generation.